2015
DOI: 10.4103/2348-8093.155518
|View full text |Cite
|
Sign up to set email alerts
|

Association of waist circumference with atherogenic cardiovascular risks in centrally obese Myanmar male subjects

Abstract: includes hypercholesterolemia, elevated low-density lipoprotein-cholesterol (LDL-C), low high-density lipoprotein cholesterol (HDL-C), hypertriglyceridamia and high atherogenic indices. [2] Serum total cholesterol (TC) levels have been shown to be consistently related to coronary heart disease (CHD) risk in many populations. [3,4] Mathematically calculated value of serum LDL-C is commonly used to estimate how much LDL-C is driving progression of atherosclerosis. [5] According to United State National Cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…AIP is being used by some practitioners as a significant predictor of atherosclerosis. It has been suggested that AIP values of <0.1 are associated with low, 0.1 to 0.24 with medium and above 0.24 with high cardiovascular risk [7]. We have studied AIP & observed a significant increase in an AIP ratio of 0.246 in cases when compared to controls (0.106).…”
Section: Fig-3: Comparison Of Cri I and Ii Ac Values In Controls And Casementioning
confidence: 78%
“…AIP is being used by some practitioners as a significant predictor of atherosclerosis. It has been suggested that AIP values of <0.1 are associated with low, 0.1 to 0.24 with medium and above 0.24 with high cardiovascular risk [7]. We have studied AIP & observed a significant increase in an AIP ratio of 0.246 in cases when compared to controls (0.106).…”
Section: Fig-3: Comparison Of Cri I and Ii Ac Values In Controls And Casementioning
confidence: 78%
“…Thus, incorporation of both HOMA-IR and AIP should be done as a standard risk assessment tool towards the development of atherosclerosis and to assess its relationship with IR. [33] When the individual parameters were used to quantify the burden of CMD risk among the study population, the obtained prevalence was comparatively less. On estimating IR by HOMA-IR with the help of FPG and FPI, 28.9% of them showed IR.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, only one review of six studies exists; it is over 15 years old and does not represent the current literature [ 13 ]. This is important because over recent years, many studies have investigated AIP and numerous have revealed a positive association between AIP and cardiometabolic risk factors [ 14 , 15 , 16 , 17 , 18 ]. Moreover, they found that an AIP value of under 0.11 is associated with a low risk of CVD, and values between 0.11 to 0.21 and upper than 0.21 are associated with intermediate and increased risks, respectively [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%